Perspectives of Implementers on the Student Teacher Practicum Program of a Philippine University: Inputs for Program Improvement - Generoso N. Mazo (Journal of Education and Learning (EduLearn), 2015)
This study sought to determine the perspectives of the 316 program implementers of the Student Teacher Practicum Program in the Leyte Normal University, Tacloban City. Using the descriptive survey method the inquiry focused on the importance, objectives, relevance, and competencies of the program. The Statistical Program for Social Sciences (SPSS) was used to test the level of significance between the perspectives of “in-campus” and “off-campus” respondents. The implementers construed the program as Very Important, Very Effective in attaining its objectives, Very Relevant, and the competencies Very Useful. The null hypotheses were not rejected on the aspects of importance, attaining the objectives and competencies while on the aspect of relevance it was rejected.